Oral lymphangioma - Case reports and review of literature - S Sunil; Devi Gopakumar; B S Sreenivasan (Wolters Kluwer Medknow Publications, 2012)
Lymphangioma is a benign hamartomatous hyperplasia of lymphatic vessels. Majority of them are superficial, but a few may extend deeply into the connective tissue. Intraoral lymphangiomas occur more frequently on the dorsum of tongue, followed by palate, buccal mucosa, gingiva, and lips. Surgical excision is the treatment of choice. The prognosis is good for most patients, although large tumors of neck/tongue may result in airway obstruction and death. This case report series discusses the clinical features, histopathology, and treatment of lymphangioma.